THE INFLUENCE OF MOTIVATION, CREATIVITY, AND FAMILY ENVIRONMENT ON INTEREST IN ENTREPRENEURSHIP IN STUDENT ENTREPRENEURSHIP COMMUNITIES RIAU HIGH SCHOOL OF ECONOMICS - Nova Riani; Winanda Marito; Padian Adi Salamat Siregar (Jurnal Scientia, 2023)
Ability communication mathematical is Wrong One ability in mathematic Which fundamental Which must mastered by Student. Through communication, there is a process of conveying ideas or ideas verbally or verbally writing so that create something understanding. This study aims to determine the effect of the Problem Based Learning learning model on mathematical communication skills and student learning outcomes in economics mathematics courses. The subjects in this study were third semester students at the Indonesian Community Development University. This study uses quantitative research, namely experiments. The results of the research that has been done show that the use of the model learning Problem based Learning influential to results Study economic mathematics and mathematical communication skills third semester students at Pembinaan Indonesia University. This is indicated by sig price . (2-tailed) is smaller than the alpha price, which is 0.000 (0.000 < 0.05) which means that there is a significant difference between the difference in pre-test scores with post-test on groups control and experimental group.